Chapter Traveling towards fame: Albert Einstein and the Eddington eclipse expedition to Príncipe and Sobral in 1919 - Casetti, Lapo (Studi e saggi, 2021)
Albert Einstein abruptly rose to worldwide fame in November 1919, after Arthur Eddington announced the successful measurement of the gravitational light bending predicted by Einstein's general theory of relativity. The measurement had been performed by an expedition towards two remote Portuguese-speaking destinations, the island of Príncipe in equatorial Africa and Sobral in northern Brazil, where the total solar eclipse of May 29, 1919 was visible and allowed to measure the position of stars close to the Sun, revealing the sought-after effect. This journey was the beginning of a story that still goes on today.